Rakawi Language in the Past and Present Time - Alit Geria, A.A. Gde Alit Geria; Weda Kusuma, I Nyoman Weda Kusuma; Suastika, I Made Suastika; Suarka, I Nyoman Suarka (e-Journal of Linguistics, 2013)
Jawa Kuna is one of the oldest documentary languages that has the richest materials as well as fine and noble national cultural values. Jawa Kuna is the key to revealing the history of the cultural life in Indonesia in the past. Therefore, studying Jawa Kuna is like digging up the “hidden pearl” because the scintillating beam or supreme (adiluhung) teachings implied in it can be used as guidance ( s?suluh ) in everyday life. A very strong desire of the experts of Jawa Kuna to discover the history and the richness of culture in the ancient time has succeeded in changing the image of Jawa Kuna from being “a distant jungle, scary and horrible” into “a virgin forest that is very close, friendly and attractive”. In Bali, the influence of Jawa Kuna has existed since the 10 th century until the globalization era nowadays. Jawa Kuna has been greatly cherished by the rakawi in creating a piece of literature ( parwa, kakawin ) until the beginning of the 21 st century. As a media in exploring the Hindu and Buddhist literature, Jawa Kuna language is preserved not merely in the sense that it is read, sung and discussed, but it is also shown with the creation of  new Kakawin using Jawa Kuna language by Balinese Rakawi (authors) namely Made Degung, I Wayan Mandra, and I Wayan Pamit. Those three Balinese rakawi have been able to comprehend one similar problem ( Siwa-Buddha ) by using the same h y pogram as well ( Siwagama ), and then it is packed in their own style into a very beautiful piece of kakawin ( langö ).
Keywords: Jawa Kuna, adiluhung (supreme), rakawi, and moral-spiritual